A new approach based on CXCR4-targeted combination liposomes for the treatment of liver fibrosis. (14th April 2022) - Ullah, Aftab; Chen, Gang; Yibang, Zhang; Hussain, Abid; Shafiq, Muhammad; Raza, Faisal; Liu, Daojun; Wang, Kaikai; Cao, Jin; Qi, Xueyong
Abstract : We propose a chemokine receptor 4 (CXCR4)-targeted combination (CTC) liposomal therapy to treat carbon tetrachloride (CCl4 )-induced liver fibrosis. CTC lipo reverses the liver fibrosis to normalization. Abstract : Liver fibrosis results from excessive extracellular matrix accumulation due to injury and leads to cirrhosis, cancer, and death. Herein, we propose a chemokine receptor 4 (CXCR4)-targeted combination (CTC) liposomal therapy to treat carbon tetrachloride (CCl4 )-induced liver fibrosis in a mouse model. This study aims to combine small molecules such as pirfenidone and AMD3100 in a single nanoplatform to investigate their synergistic antifibrotic effects in a setting of CCl4 -induced liver fibrosis. CTC liposomes (CTC lipo) were prepared using the thin-film hydration method. CTC lipo exhibited a spherical shape, and the particle size was recorded at the nanoscale which confirms its appropriateness for in vitro and in vivo applications. CTC lipo had good storage and serum stability. The entrapped drugs in CTC lipo showed reduced toxicity at higher concentrations. CTC lipo displayed CXCR4 mediated cell uptake and were internalized by caveolae-mediated endocytosis. CTC lipo showed CXCR4 targeting and stromal cell-derived factor 1α (SDF1-α)/CXCR4 axis blocking activity. CTC lipo reduced the elevated serum aspartate aminotransferase (AST), alanine transaminase (ALT), and hydroxyproline (HYP) levels. The histological studies showed improved liver architecture and reduced collagen deposition after treatment. Transforming growth factor β (TGFβ), alpha-smooth muscle actin (α-SMA), and collagen I were elevated by CCl4 in comparison with the Sham. Upon CTC liposomal treatment, the quantitative score for the elevated fibrotic proteins such as TGFβ, α-SMA, and collagen I was normalized. CTC lipo displayed significant downregulation of the upregulated TGFβ, α-SMA, collagen I, and P-p38 expressions at the molecular level. The CXCR4 targeted liposomes showed prolonged biodistribution at 24 h. Our findings indicated that CTC lipo might be an alternative antifibrotic therapy that may offer new access to research and development. In a nutshell, the present study suggests that systemic administration of CTC lipo has efficient antifibrotic potential and deserves to be investigated for further clinical applications.